Ferropericlase inclusions in ultradeep diamonds from Sao Luiz (Brazil): high Li abundances and diverse Li-isotope and trace element compositions suggest an origin from a subduction mélange - Seitz, Hans-Michael; Ludwig, Thomas (Mineralogy and petrology, 2018)
The most remarkable feature of the inclusion suite in ultradeep alluvial and kimberlitic diamonds from Sao Luiz (Juina area in Brazil) is the enormous range in Mg# [100xMg/(Mg + Fe)] of the ferropericlases (fper). The Mg-richer ferropericlases are from the boundary to the lower mantle or from the lower mantle itself when they coexist with ringwoodite or Mg- perovskite (bridgmanite). This, however, is not an explanation for the more Fe-rich members and a lowermost mantle or a “D” layer origin has been proposed for them. Such a suggested ultra-deep origin separates the Fe-rich fper-bearing diamonds from the rest of the Sao Luiz ultradeep diamond inclusion suite, which also contains Ca-rich phases. These are now thought to have an origin in the uppermost lower mantle and in the transition zone and to belong either to a peridotitic or mafic (subducted oceanic crust) protolith lithology. We analysed a new set of more Fe-rich ferropericlase inclusions from 10 Sao Luiz ultradeep alluvial diamonds for their Li isotope composition by solution MC-ICP-MS (multi collector inductively coupled plasma mass spectrometry), their major and minor elements by EPMA (electron probe micro-analyser) and their Li-contents by SIMS (secondary ion mass spectrometry), with the aim to understand the origin of the ferropericlase protoliths. Our new data confirm the wide range of ferropericlase Mg# that were reported before and augment the known lack of correlation between major and minor elements. Four pooled ferropericlase inclusions from four diamonds provided sufficient material to determine for the first time their Li isotope composition, which ranges from δ7Li + 9.6 ‰ to −3.9 ‰. This wide Li isotopic range encompasses that of serpentinized ocean floor peridotites including rodingites and ophicarbonates, fresh and altered MORB (mid ocean ridge basalt), seafloor sediments and of eclogites. This large range in Li isotopic composition, up to 5 times higher than ‘primitive upper mantle’ Li-abundances, and an extremely large and incoherent range in Mg# and Cr, Ni, Mn, Na contents in the ferropericlase inclusions suggests that their protoliths were members of the above lithologies. This mélange of altered rocks originally contained a variety of carbonates (calcite, magnesite, dolomite, siderite) and brucite as the secondary products in veins and as patches and Ca-rich members like rodingites and ophicarbonates. Dehydration and redox reactions during or after deep subduction into the transition zone and the upper parts of the lower mantle led to the formation of diamond and ferropericlase inclusions with variable compositions and a predominance of the Ca-rich, high-pressure silicate inclusions. We suggest that the latter originated from peridotites, mafic rocks and sedimentary rocks as redox products between calcite and SiO2.
Gesehen am 27.09.2019